Endoscopic Adhesiolysis of the Flexor Hallucis Longus Muscle. Issue 6 (December 2014) - Lui, T.H.
Flexor hallucis longus muscle can adhere to the distal tibia after tibial fracture. The patient may complain of deep posteromedial ankle pain, checkrein deformity of the hallux, hallux flexus or development of hallux rigidus. Surgical treatment of release of the FHL muscle or lengthening of the FHL tendon has been proposed. We described an endoscopic approach of release of the FHL muscle from the distal tibia with the advantage of minimal soft tissue dissection. Level of Evidence: Therapeutic Level V: Expert Opinion/Technique